Packaging environmental impact on seafood supply chains: A review of life cycle assessment studies. (24th August 2021) - Almeida, Cheila; Loubet, Philippe; da Costa, Tamíris Pacheco; Quinteiro, Paula; Laso, Jara; Baptista de Sousa, David; Cooney, Ronan; Mellett, Sinead; Sonnemann, Guido; Rodríguez, Carlos José; Rowan, Neil; Clifford, Eoghan; et al.
Abstract: Packaging is fundamental for food preservation and transportation but generates an environmental burden from its production and end‐of‐life management. This review evaluates packaging contribution to the environmental performance of seafood products. Life cycle assessment (LCA) studies were evaluated by both qualitative and quantitative analysis. The qualitative analysis assessed how direct (e.g., packaging material) and indirect impacts (e.g., influence on seafood loss and waste) have been considered, while the quantitative analysis evaluated packaging contribution to products' weight and climate change impact. Qualitative analysis revealed that seafood LCAs focus mainly on direct environmental impacts arising from packaging materials, for which some articles conducted sensitivity analysis to assess materials substitution. Recycling was found to be the most common recommendation to diminish direct potential environmental impacts arising from packaging end‐of‐life. However, standardized recovery rates and other end‐of‐life options (e.g., reuse), should be considered. Quantitative analysis revealed that cans' production contributes significantly to the overall climate change impact for canned products. On average, it contributes to 42% of a product's climate change impact and 27% of a product's weight. Packaging has a lower contribution when considering freezing, chilling, and other post‐harvesting processing. It represents on average less than 5% of a product's climate change impact (less than 1 kg CO2 eq/kg) and 6% of a product's weight. Packaging material production is more relevant to aluminum, tinplate, and glass than for plastic and paper. Therefore, it is essential to accurately include these materials and their associated processes in inventories to improve the environmental assessment of seafood products.